2006
DOI: 10.1002/elps.200600030
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis for the analysis of small‐molecule pharmaceuticals

Abstract: This paper reviews the application of CE to the analysis of small-molecule pharmaceuticals. The areas of pharmaceutical analysis covered are enantiomer separation, the analysis of small molecules such as amino acids or drug counter-ions, pharmaceutical assay, determination of related substances and physicochemical measurements such as log P and pK(a) of compounds. The different electrophoretic modes available and their advantages for pharmaceutical analysis are described. Recent applications of CE for each sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 197 publications
0
56
0
3
Order By: Relevance
“…Driving forces in CE are electrophoretic migration and the electro-osmotic flow (EO F ) . C E h a s b e c o m e a u s e f u l t o o l i n pharmaceutical analysis because of its advantages over other separation techniques, such as high resolution, high selectivity, simplicity, short analysis time, cost efficiency and low consumption of solvents and reagents [102]. Mainly employed CE modes for drug analysis are capillary zone electrophoresis (CZE) based on charge-to-mass ratio and micellar electrokinetic chromatography (MEKC) based on chromatographic partition of analytes between micelles and background electrolyte.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…Driving forces in CE are electrophoretic migration and the electro-osmotic flow (EO F ) . C E h a s b e c o m e a u s e f u l t o o l i n pharmaceutical analysis because of its advantages over other separation techniques, such as high resolution, high selectivity, simplicity, short analysis time, cost efficiency and low consumption of solvents and reagents [102]. Mainly employed CE modes for drug analysis are capillary zone electrophoresis (CZE) based on charge-to-mass ratio and micellar electrokinetic chromatography (MEKC) based on chromatographic partition of analytes between micelles and background electrolyte.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…Due to the vast exploration in this subject, numerous reviews detailing fundamentals and applications can be found in the literature prior to 2005 [6][7][8][9][10][11] and over the past two years [12][13][14][15]. Reviews have also covered methods developed specifically for pharmaceutical compounds [16][17][18][19][20][21][22], biological compounds [23], chiral LC-MS/ CE-MS [24], pesticides [25], pollutants [26], and food additives [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The use of CE in the pharmaceutical analysis has increased in recent years and includes drug assays, chiral separation, and analysis of pharmaceutical excipients of drug related impurities. 11) CE separations are generally more efficient, can be performed faster and require only nanoliter injection volumes. 12) Capillary zone electrophoresis (CZE) and micellar electrokinetic chromatography (MEKC) are the two most widely used separation modes of this technique.…”
Section: )mentioning
confidence: 99%